Changes in referral pathway and phenotypic status of patients diagnosed with ATTR cardiac amyloidosis during the past 20 years. (3rd October 2022) - Ioannou, A; Patel, R K; Razvi, Y; Porcari, A; Venneri, L; Bandera, F; Masi, A; Williams, G E; O'Beara, S; Ganesananthan, S; Martinez-Naharro, A; Chacko, L; et al.
Abstract: Background: Diagnostic and therapeutic advances have led to much increased awareness of transthyretin (ATTR) cardiac amyloidosis (CA). Purpose: We sought to characterise the impact of this on referral practice, cardiac phenotype at diagnosis and specifically to determine whether patients are now being diagnosed at an earlier stage in their disease process. Methods: We studied 1845 patients diagnosed with ATTR-CA at the National Amyloidosis Centre (NAC) from 2002–2021, all of whom underwent deep clinical phenotyping and follow-up. Results: Analysis by 5-year quartiles revealed a substantial incremental increase in patients diagnosed with ATTR-CA (35 vs 260 vs 704 vs 846), which was associated with greater proportions of patients referred following advanced cardiac imaging (referrals following cardiac magnetic resonance and bone scintigraphy: 3% vs 44% vs 67% vs 76%; P<0.001). Over time, median duration of symptoms prior to diagnosis diminished from 36-months between 2002–2006 to 12-months between 2017–2021 (P<0.001) and a greater proportion of patients presented with milder disease across the 5-yearly quartiles (NAC stage 1: 40% vs 43% vs 44% vs 57%; P<0.001). The latter was associated with more favourable echocardiographic parameters of structure and function, including an incremental reduction in maximal left ventricular wall thickness (18.26mm vs 17.41mm vs 17.09mm vs 16.68mm; P=0.017). This was associated with improved survival in the overall population (2007–2011 vs 2012–2016: HR=1.65, 95% CI [1.33–2.06]; P<0.001 and 2012–2016 vs 2017–2021: HR =1.83, 95% CI [1.45–2.31]; P<0.001) and in each genotype (wtATTR, T60A and V122I). Despite a significant increase in the proportion of patients enrolled into clinical trials (0.0% vs 0.0% vs 2.6% vs 23.9%; P<0.001) and prescribed disease modifying therapy (5.7% vs 0.4% vs 4.8% vs 13.5%; P<0.001); the improved survival remained significant even after adjusting for clinical trials and disease modifying therapy (2012–2016 vs. 2017–2021: HR=1.65 95% CI [1.29–2.11], P<0.001). Conclusion: Increased awareness and advances in cardiac imaging have been associated with a substantial increase in the diagnosis of ATTR-CA and at a progressively earlier stage of the disease, which has contributed to improved survival in recent years. These changes may have important implications for initiation and outcome of therapy. Given that ATTR-CA is now being diagnosed earlier, more data are needed to guide decisions on in whom and when to initiate treatment, and which treatments should be used at each disease stage. Furthermore, the changes in ATTR-CA phenotype at diagnosis urgently need to be factored into clinical trial design, given that pre-determined end-points based on trials performed in the past may no longer be appropriate, or at least sufficiently powered, or of adequate duration to evaluate efficacy of novel agents. Funding Acknowledgement: Type of funding sources: None.